Analisis Implementasi Pembelajaran Daring Pada Masa New Normal (Studi Kasus di Program Studi S1 Pendidikan Ekonomi FKIP UKSW Salatiga) - Eka Yuliana Rahmawati; Arief Sadjiarto; Tri Nugroho Budi Santoso (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze the implementation of online learning during the New Normal at the SWCU Salatiga FKIP Economic Education Study Program. This research was a qualitative descriptive case study involving informants, namely the Head of Study Program, Lecturers, and Students. Data collection techniques are interviews, observation, and documentation. Meanwhile, the data analysis technique used was the Miles and Huberman Interactive model, namely the stages of data collection, data reduction, data presentation, and concluding/verification. The results showed that the implementation of online learning in the SWCU Salatiga FKIP Economic Education Undergraduate Study Program had been running well and effective. The ability of lecturers in managing the online learning was good, student responses during the implementation of online learning were quite good, students and lecturers already had the facilities needed to support the implementation of the online learning. The implementation of online learning was felt to be more flexible, some students felt more active, and could hone their skills and improve the ability of students and lecturers to use and operate technology. Common obstacles were network constraints and some students found that material delivered online was sometimes difficult to understand.